1992
DOI: 10.1152/ajprenal.1992.263.5.f769
|View full text |Cite
|
Sign up to set email alerts
|

Induction and intracellular localization of HSP-72 after renal ischemia

Abstract: To determine whether heat shock proteins (HSPs) might be active in cellular recovery following transient ischemia, we examined rat kidneys for 70-kDa HSP (HSP-70) mRNA expression, protein elaboration, and intracellular localization after 45 min of renal ischemia and reflow of 15 min, 2, 6, and 24 h. Inducible HSP-70 mRNA is present at 15 min of reperfusion, peaks between 2 and 6 h, and falls by 24 h. Inducible 72-kDa HSP (HSP-72) protein accumulates progressively through 24 h and is found in both soluble and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 0 publications
7
55
0
Order By: Relevance
“…An increasing body of indirect evidence suggests that interaction between HSP72 and NKA occurs in both in vitro and in vivo renal ischemic injury. Van Why et al (19) detected a similar localization and granulation pattern between HSP72 and the NKA ␣ 1 -subunit in postischemic kidneys. Ischemic preconditioning with HSP72 overexpression prevented NKA ␣ 1 -subunit dissociation after repeated ischemic insult (1).…”
Section: Discussionmentioning
confidence: 80%
“…An increasing body of indirect evidence suggests that interaction between HSP72 and NKA occurs in both in vitro and in vivo renal ischemic injury. Van Why et al (19) detected a similar localization and granulation pattern between HSP72 and the NKA ␣ 1 -subunit in postischemic kidneys. Ischemic preconditioning with HSP72 overexpression prevented NKA ␣ 1 -subunit dissociation after repeated ischemic insult (1).…”
Section: Discussionmentioning
confidence: 80%
“…Vicencio et al (8) have demonstrated a temporal correlation between a peak of HSP72 protein expression and a consequent protection of immature animals against hypoxic renal injury. In experimental ARF, renal ischemia has been shown to induce HSP72 synthesis during recovery of the proximal tubular cells (15), and low levels of HSP72 have been considered as detrimental for renal recovery (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of this upregulation, however, remains unknown. Interestingly, the endogenous cellular injury signals that can activate TLR2, such as heat shock proteins (6), and the contents of necrotic cells (7) are known to accumulate upon renal ischemic tissue injury (8,9).…”
Section: Introductionmentioning
confidence: 99%